The Effect of Selected Chemical Preservatives and Starter Cultures on the Sensory Characteristics and Shelf Life of Rice Injera - Hassen, Yassin; Muzira Mukisa, Ivan; Kurabachew, Henok (Journal of Bioprocessing & Biotechniques, 2018)
Injera is yeast-risen flat bread with a unique, slightly spongy texture. It is a national staple in Ethiopia that is eaten daily in virtually every household. Rice injera has a very short life (2-3 days) at room temperature and essentially spoils due to mould growth. The use of weak organic acid as preservative is allowed in acidic foods, primarily as mould inhibitors. In this study, the effects of chemical preservatives: benzoic acid, sodium benzoate, and potassium sorbate and starter cultures (Lactobacillus plantarum+Saccharomyces cerevisiae) on the quality and shelf life of rice injera were investigated. Benzoic acid (0.1%), sodium benzoate (0.1%), potassium sorbate (0.2%) and a 1:1:1 blend of the three (0.2%) were added immediately before baking. Qualitative descriptive analysis (n=10) was used to describe the characteristics of the injera samples. A consumer acceptability panel (n=30) was used to determine the acceptability and shelf life of injera. The preservatives significantly (p<0.05) prolonged the shelf life of injera for up to 10 days with the combination of the three starters achieving the greatest effect. The findings of this study showed that the rice injera prepared with chemical preservatives (0.1 benzoic acid, 0.2% potassium sorbate, 0.1% sodium benzoate and 0.2% of the three preservatives retains maximum overall acceptability. Rice injera produced under controlled fermentation L. plantarum, and S. cerevisiae produce injera with better sensory quality than the traditional by using Irsho. Nine descriptors/attributes describing appearance, aroma/odor, taste, and texture were generated to characterize the sensory properties of rice injera. Softness, rollablity, fluffiness, eye size, whitness of top and bottom surfaces and slight sour taste are main characterstics descriptors of rice injera. Softness, fluffiness, spongness, slight sourness and eye size are attributes associated with quality of rice injera. Therefore, a starter combination of L. plantarum+S. cerevisiae together with 0.2% of the blend of the preservatives (0.1% benzoic acid+0.1% sodium sorbate+0.2% potassium sorbate) in 1:1:1 ratio preservatives can be used to produce acceptable injera with a shelf life of 10 days at room temperature.
Keywords: Rice injera; Sensory attributes; Benzoic acid; Potassium sorbate; Sodium benzoate